Dynamics of Water Quality for Vannamei Shrimp Cultivation in Intensive Ponds in Coastal Areas - Rizky Kusma Pratiwi; Mohammad Mahmudi; Abdul Rahem Faqih; Diana Arfiati (Jurnal Penelitian Pendidikan IPA, 2023)
Cultivators increase production using intensive cultivation which applies stocking densities and feeding in high quantities, which triggers a decrease in water quality, both cultivation water and cultivation wastewater because it contains high levels of organic matter. Changes in water quality have an impact on plankton community structure. This research aims to determine the dynamics of the physical, chemical, and biological quality of cultivation media water and the disposal of vaname shrimp cultivation waste in Ujungpangkah District, Gresik Regency. The research was conducted in January 2023 using a survey method. Water and plankton samples were taken from reservoirs, ponds, and pond waste disposal sites. Sampling was carried out in vaname shrimp cultivation ponds in the Coastal Area of ​​Ujungpangkah District, Gresik Regency. The physical and chemical quality of water has a pattern of changes up and down but is relatively the same and stable every week. All of these water quality parameters show a pattern of change that is quite good for the growth of vaname shrimp, but in waste disposal, the parameters for nitrate, phosphate, ammonia, and TOM are above the quality standards. The highest abundance of plankton is in waste dumps, with the highest phytoplankton coming from the Bacillariophyta phylum (49%), while zooplankton comes from the Rotifera phylum (54%). Regular monitoring of water quality in ponds and waste disposal sites is required so that it remains stable and safe for the environment.